2006
DOI: 10.1109/tcad.2006.870411
|View full text |Cite
|
Sign up to set email alerts
|

Hardware compilation of application-specific memory-access interconnect

Abstract: Abstract-A major obstacle to successful high-level synthesis (HLS) of large-scale application-specified integrated circuit systems is the presence of memory accesses to a shared-memory subsystem. The latency to access memory is often not statically predictable, which creates problems for scheduling operations dependent on memory reads. More fundamental is that dependences between accesses may not be statically provable (e.g., if the specification language permits pointers), which introduces memory-consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…At the very least, ESL flow is supposed to incorporate a front-end with higher level specifications (e.g., SystemC or ANSI-C) into synthesis flow. There are several interesting publications related to ESL flow for asynchronous (bundled delay) design [44], [114], [115]. This flow is actually closer to a software C-compiler than a hardware synthesis flow.…”
Section: Examples and Discussionmentioning
confidence: 99%
“…At the very least, ESL flow is supposed to incorporate a front-end with higher level specifications (e.g., SystemC or ANSI-C) into synthesis flow. There are several interesting publications related to ESL flow for asynchronous (bundled delay) design [44], [114], [115]. This flow is actually closer to a software C-compiler than a hardware synthesis flow.…”
Section: Examples and Discussionmentioning
confidence: 99%
“…However, while most other studies focus on algorithmic-centric reconfigurable computing architectures, our study focuses primarily on how to exploit memory-level parallelism. Recently, extracting memorylevel parallelism in reconfigurable computing has attracted more attention [28][29][30][31]. For example, recent work [32] proposed a many-cache memory architecture that improves caching in commercially available FPGAs.…”
Section: Related Workmentioning
confidence: 99%
“…Budiu et al identified two primary bottlenecks in their work: significant latency overheads due to a deeply pipelined memory arbitration tree that is necessary to support parallel memory requests [6], as well as performance constraints due to complex control flow [8]. Other projects have attempted to optimize the memory access network for custom hardware by either optimizing for the most frequent accesses [31], partitioning and distributing memory [25], or incorporating cache-like structures [32], [5]. Tartan, a reconfigurable architecture for spatial computation was also developed [33].…”
Section: Related Workmentioning
confidence: 99%